Determinants of Filipino children's responses to the death of a sibling. - Atuel, Teodora M.
Problem: 1. What are young children's reactions to the death of a sibling? 2. Are factors such as sex of the surviving child, age of the child who died, nature of the death, time interval following sibling's death, and socioeconomic status (SES) related to a young child's reactions to the death of sibling? Method: Survey. Ss: 73 school age children, all Catholics and with siblings who have died within a year from the start of data collection located through the registries of 4 government and 1 private hospital, as well as the municipal registries of Pateros, Taguig, Makati, Las Pinas, and Marikina. Instruments: interview schedule and projective test pictures. Statistics: 1. frequency and percentage distributions; and 2. Chi-square test, and sign test. Findings: 1. The grief reactions verbalized by the children which were classified into 3 stages (immediate, intermediate, and final) when associated with the independent variables showed that age of the dead child (toddler, preschool and school age), time interval since death (less than or over 6 months) and socio economic status (low or upper/middle) significantly influenced the stages of grief. 2. Meanwhile, age of the dead child and nature of death (chronic or sudden) significantly affected their fear-related story productions elicited by the projective test. 3. Regarding school grade, three-fourths of the children's grades became significantly lower following the death of the sibling, regardless of other variables. 4. Both the typical reactions of the children in each stage and the specific affective responses of death imagery/theme and loneliness theme/imagery are featured.